Sauropus androgynus L. Merr.-A phytochemical, pharmacological and toxicological review - Zhang, Bo-dou; Cheng, Jia-xin; Zhang, Chao-feng; Bai, Yi-dan; Liu, Wen-yuan; Li, Wei; Koike, Kazuo; Akihisa, Toshihiro; Feng, Feng; Zhang, Jie (Journal of ethnopharmacology, 2020)
Sauropus androgynus L. Merr is an underexploited perennial shrub traditionally used as a medicinal plant in South Asia and Southeast Asia. The plant is regarded as not just a green vegetable for diet, but as a traditional herb for certain aliments. For instance, it has traditionally been used to relieve fever, to treat ulcers and diabetes, to promote lactation and eyesight, and to reduce obesity. This paper aims to review the botany, phytochemistry, ethnopharmacology, and pharmacological activities of S. androgynus, and discuss the known chemical constituents at work in S. androgynus-induced bronchiolitis obliterans for providing new ideas to the mechanism of the disease and pharmacology research of the plant. The data presented in this review were collected from published literatures as well as the electronic databases of PubMed, CNKI, Web of Science, SCI finder, ACS, Science Direct, Wiley, Springer, Taylor, Google Scholar, and a number of unpublished resources, (e.g. books, and Ph.D. and M.Sc. dissertations). The scientific literature indicates that S. androgynus is a valuable and popular herbal medicine whose nutritional value is also higher than that of other commonly used vegetables. Phytochemical analyses identified high content of fatty acids, flavonoids, and polyphenols as the major bioactive components in S. androgynus. Crude extracts and phytochemical compounds isolated from S. androgynus show a wide spectrum of in vitro and in vivo pharmacological activities such as antioxidant, anti-inflammatory, anti-ulcer, skin whitening, anti-diabetic, and immunoregulatory activities. The traditional use, such as increasing lactation, treating ulcers and diabetes, and reducing obesity, have been evaluated and studied with various methods. Numerous reports have revealed the unusual link between the consumption of S. androgynus and the induction of a chronic and irreversible obstructive disease (namely, bronchiolitis obliterans), indicating that the toxicity and side effects of this plant that is presently used in health care and medicine are a major area of concern. Though little importance was attached to this green plant, S. androgynus has notable phytochemical constituents and various pharmacological activities including antioxidant, anti-inflammatory, and anti-obesity activities. Studies have firmly established the association between excessive consumption of the uncooked S. androgynus juice over a period of time and the occurrence of bronchiolitis obliterans. It is inadvisable to ingest excessive amounts of S. androgynus before fully understanding the pathogenesis and induction mechanism of this fatal disease. The phytochemistry of S. androgynus, its pharmacology for traditional use, S. androgynus-induced bronchiolitis obliterans still need further investigation.